Adult parenteral nutrition in the North of England: a region-wide audit. Issue 1 (10th January 2017) - Dyson, Jessica K; Thompson, Nick
Abstract : Objectives: Parenteral nutrition (PN) is widely used to provide nutritional support to patients with inaccessible or inadequate length of gut or non-functioning gut. The objective was to compare practice in PN administration to results of the National Confidential Enquiry into Patient Outcome and Death (NCEPOD) report, 'A Mixed Bag', and to establish whether good practice was being followed within this part of the UK. Setting: Using the Northern Nutrition Network (NNN), we examined the care of adult patients receiving PN in all 10 secondary care hospitals in our region. Participants: All patients receiving PN were included with no exclusions. Data were collected on 192 patients (51% females, median age 65 years (range 18–96)). Outcome measures: A data collection tool was designed based on the recommendations of the NCEPOD report. Results: PN was used for a median of 7 days with a 30-day mortality rate of 8%. Metabolic complications occurred in 34%, of which only 13% were avoidable. The catheter sepsis rate was 1.5 per 1000 PN days. The audit suggests that nutrition team input improves patient assessment prior to starting PN and review once PN is established. Risk of refeeding syndrome was identified in 75%. Areas for improvement are documentation of treatment goal (39%), review of PN constitution (38%), ensuring patients are weighed regularly (56%) and documentation of line-tip position (52%). Conclusions: This region-wide prospective audit suggests improved practice within the UK compared to the NCEPOD audit with lower mortality and line sepsis rates. However, documentation remains suboptimal. This work strengthens the case for introducing nutrition teams in hospitals without this service. These findings are likely to be reproduced across the UK and in other healthcare settings. We provide a template for similar audits of clinical practice.